Responding to COVID-19 With the Aid of Mutually Beneficial Partnerships in Education - Biag, Manuelito; Gomez, Louis M.; Imig, David G.; Vasudeva, Ash (Frontiers in Education, 2021)
The COVID-19 pandemic has quickly altered the structures and routines of K-12 education around the world. Districts and schools across the world continue to adapt their ways of working to address a variety of challenges, many of whose dimensions are complex, dynamic, and not entirely known. Absent cooperation and collaboration among stakeholders, institutions, and communities, we will be unable to address the learning, social, and emotional needs of students. In this paper, we present evidence that suggest mutually beneficial LEA-IHE partnerships, grounded in improvement science, can serve as an important resource to address dilemmas brought about by the pandemic. Examining the work of four partnerships in the Improvement Leadership Education and Development (iLEAD) Network, we show how these partnerships address the complexities of COVID-19. The results suggest what matters is that they take a systems-perspective, pay close attention to the needs of key users, avoid pre-determined programs or solutions, and engage in disciplined inquiry across institutional boundaries to affect positive and lasting change. Understanding the mechanics of how these district-university partnerships operate – their principles, routines, methods, and tools – can help educational systems support students during this time of great uncertainty